Implementation of good practices for promotion of personnel and their relationship with the organization's commitment and culture (2010)
The research hypothesizes and tests a model of relationships between the values of the organizational culture, implementation of a good practice for promotion of personnel from the perspective of gender and commitments to the organization. To test the hypothesis, a structural equations model was employed and a survey was carried out among 425 employees. The results led to the conclusion that values that are removed from power and long-range orientation predict the implementation of good practices for the promotion of personnel; the components of commitments to the organization did not show significant associations with implementation of a good practice for the promotion of personnel. The study contributes towards developing a body of research into the implications of the gender perspective at organizations.